Perangkat Edukasi Pasien dan Keluarga dengan Media Booklet (Studi Kasus Self-Care Diabetes Melitus) - Lilik Pranata; Sri Indaryati; Novita Elisabeth Daeli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to see the effect of education with the booklet on self-care diabetes knowledge. The method in this research is quantitative research with one group pretest-posttest queasy experimental design. The results showed that the Wilcoxon statistical test obtained p-value = 0.000 <0.05, which means a significant difference in the pre-test and post-test knowledge of 22 respondents. The average change in intervention before the intervention was 12.80, and intervention was 16.32. In conclusion, patient and family education using booklets provides a shift in knowledge of diabetes mellitus self-care. Keywords: Booklet, Diabetes Mellitus, Knowledge, Personal Care